Predicting early functional outcomes in aneurysmal subarachnoid hemorrhage in endovascular coiling and surgical clipping - Chu, Liang; Cao, Kan; Jiang, Kuan; Lu, Yunpeng; Qi, Ming; Wu, Da (Frontiers in Neurology, 2025)
ObjectivesThis study aimed to evaluate early functional outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH) treated with either endovascular coiling or surgical clipping and to develop predictive models tailored to each treatment modality.Materials and methodsPatients diagnosed with aSAH were retrospectively enrolled from two hospitals in China between January 1, 2015, and December 31, 2022. Based on the treatment approach, patients were divided into two groups: endovascular coiling and surgical clipping. Independent risk factors were identified using least absolute shrinkage and selection operator (LASSO) regression followed by multivariate logistic regression. The relative contribution of each significant factor was calculated, and nomograms were constructed accordingly. Model performance was subsequently assessed through validation analyses.ResultsMultivariate analysis identified Hunt–Hess grade, Glasgow Coma Scale (GCS) score, modified Fisher Scale (mFS), D-dimer, age, and body temperature as independent predictors of early functional outcomes following endovascular coiling (all p-values <0.05). For surgical clipping, Hunt–Hess grade, GCS score, mFS, and D-dimer emerged as significant predictors (all p-values <0.05). The calculated relative contributions for endovascular coiling were 32.78% (Hunt–Hess grade), 31.99% (mFS), 4.63% (GCS score), and 13.73% (D-dimer); for surgical clipping, these values were 33.55, 38.02, 8.44, and 19.99%, respectively. Nomograms were developed for both treatment groups, and their performance was validated using receiver operating characteristic (ROC) curves, calibration plots, and decision curve analysis (DCA), demonstrating strong discriminative ability and clinical applicability.ConclusionThis study developed predictive nomogram models for early functional outcomes of aSAH patients undergoing endovascular coiling or surgical clipping treatments, emphasizing the importance of scoring systems and clinical parameters (such as D-dimer), demonstrating strong clinical utility.